Operation characteristics and performance analysis of integrated power and hybrid cooling systems driven by PEM fuel cell. (26th April 2023) - Cai, Shanshan; Xu, Hongyang; Zou, Yuqi; Li, Song; Luo, Xiaobing; Tu, Zhengkai; Chan, Siew Hwa
Abstract: With the rapid growth in the number of data centers, energy consumption has increased exponentially, and energy conservation has become a focus of data center applications. Owing to the different ambient conditions in different regions, this study proposed novel integrated power and hybrid cooling systems driven by PEMFC. Multiple cooling methods were investigated to make full use of the waste heat generated by PEMFC and natural cold sources. Three types integrated systems, including a basic combined cooling and power (BCCP) supply system, a heat pipe combined cooling and power (HPCCP) supply system, and an outdoor air combined cooling and power (OACCP) supply system were constructed. Five cities representing five climatic regions were selected to compare and analyze the operation characteristics and energy efficiency of the three systems. It is concluded that the values of power usage effectiveness (PUE) in the three systems are 1.16–1.32, and the theoretical energy efficiency is 87.80%–91.08%, which is 11.27%–12.42% higher than the reported value of a commercially used data center in Changping. The energy efficiency of the OACCP system is generally higher than that of the HPCCP system. The HPCCP system is suitable for cold and severely cold climate regions, and the OACCP system is suitable for temperate climate regions. Such findings may provide theoretical basis for the selection of the integrated power and cooling system designed for data centers in different climate regions. However, the theoretical results may need further improvement by including the energy loss during transportation and the efficiency of the converter during power conversion. Highlights: PEMFC-CCP systems with multiple hybrid cooling methods for data centers are proposed. Collaboratively control strategies are designed for fully use natural cold sources. Annual operation performances are systematically analyzed in five typical climate regions. The optimal PEMFC-CCP system is selected in different climate regions.